Prediction of overwash in alongshore variable barrier islands [Previsão da ocorrência de galgamentos em ilhas barreira com variabilidade longilitoral] - Matias, Ana Catarina (2019)
Overwash prediction is very important for coastal zone management. This work intends to identify alongshore variations in storm impact and evaluate the role of sub-aerial and submerged morphologies in overwash occurrence. For this study, 24 cross-shore topo-bathymetric profiles were set on Barreta Island (Ria Formosa barrier island system, Portugal). Pre- and post-overwash surveys were made between August 2012 and April 2013. During overwash events, tidal levels and wave parameters at breaking were obtained. Overwash occurred under storm and non-storm conditions, the latter coincident with spring high-tide. Beach morphology was spatially variable, and changeable from one overwash episode to the next. Predictions of overwash occurrence were made using the Overwash Potential, defined as the difference between runup and barrier elevation. Several runup equations were tested, and the results compared to the actual observations. The selected predictor provided an accuracy of 88% for the identification of the locations where overwash occurred. This study proves that nearshore and foreshore morphologies have a major impact on the longshore distribution of overwash.